Electric currents induced by twisted light in quantum rings - Quinteiro, Guillermo Federico (2009)
We theoretically investigate the generation of electric currents in quantum rings resulting from the optical excitation with twisted light. Our model describes the kinetics of electrons in a two-band model of a semiconductor-based mesoscopic quantum ring coupled to light having orbital angular momentum (twisted light). We find the analytical solution, which exhibits a circular photon-drag effect and an induced magnetization, suggesting that this system is the circular analog of that of a bulk semiconductor excited by plane waves. For realistic values of the electric field and material parameters, the computed electric current can be as large as juA; from an applied perspective, this opens new possibilities to the optical control of the magnetization in semiconductors. © 2009 Optical Society of America.